Écologie et fiscalité : convergence des luttes ? - Marianne Ollivier-Trigalo (VertigO)
The 2014 Finance Bill (FDP 2014) introduced a carbon component into the Internal Tax on Consumption of Energy Products (TICPE) – also known as the climate energy contribution or carbon tax. The inclusion of this measure in the 2014 FDP is the responsibility of the government, which formally relies on the work of a Committee for Ecological Taxation (CFE), which we examined in order to understand under what conditions the introduction of the carbon base in TICPE was developed. On this empirical basis (numerous writings by the CFE and interviews with members of the committee), the purpose of this article is to highlight an interdependence between taxation and energy policy that the outcome of this work shows, reflected in the vote on the TICPE reform. Our analysis highlights how CFE members have had to deal with the rules and formats imposed by taxation. These tax rules are reflected in the choice to go through TICPE, which responds to a double injunction : on the one hand, the efficiency injunction – a tax is above all a revenue ; and on the other hand, the injunction not to create a new tax. The choice to reform TICPE has several characteristics that have a public policy meaning. The mobilisation of a tax instrument has led to the use of tax switching arguments – a tax transition. At the same time, focusing on fossil fuel consumption by introducing the consideration of CO2 emissions (including fuels) has led to exchanges on the search for energy efficiency – an energy transition. Of course, reality does not choose but, on the contrary, mixes the two orientations, making them interdependent.